2002
DOI: 10.1002/ett.4460130513
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of an OFDM system and a single carrier system using frequency domain equalization

Abstract: Abstract. In this work we compare an OFDM (Orthogonal Frequency Division Multiplexing) system and a SC/FDE (Single Carrier System with Frequency Domain Equalization) system in terms of their BER performance, channel estimation techniques, bandwidth-efficiency and other design parameters. In both systems an estimation of the channel transfer function is needed for equalization purposes. Different frequency domain based channel estimation techniques for both systems are presented and compared. BER-simulations ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…The OFDM system uses the IFFT at the transmitter for the OFDM signal multiplexing, while the FDE puts the IFFT at the receiver side to transform the equalised data back into the time domain. This similarity between the structure of FDE and OFDM has been rediscovered again and again [2,29,30]. This similarity is tremendously useful in constructing a multimode receiver.…”
Section: Software-defined Radio Based On Fdementioning
confidence: 93%
See 1 more Smart Citation
“…The OFDM system uses the IFFT at the transmitter for the OFDM signal multiplexing, while the FDE puts the IFFT at the receiver side to transform the equalised data back into the time domain. This similarity between the structure of FDE and OFDM has been rediscovered again and again [2,29,30]. This similarity is tremendously useful in constructing a multimode receiver.…”
Section: Software-defined Radio Based On Fdementioning
confidence: 93%
“…Falconer et al [2] and Witschnig et al [29], for example, mentioned the possibility to combine a single-carrier system using FDE in uplink and an OFDM system in downlink of a mobile communication system. However, since we have shown that FDE is also applicable in CDMA systems, we can then move even further.…”
Section: Software-defined Radio Based On Fdementioning
confidence: 98%
“…For OFDM, D is the IFFT block and Q is an ineffective identity matrix and vice versa for SC‐FDE. Both OFDM and SC‐FDE are cyclic prefix (CP) block transmission based techniques and utilise FFT and IFFT algorithms .…”
Section: System Modelmentioning
confidence: 99%
“…In many research works, orthogonal frequency division multiplexing (OFDM) has been employed as the antimultipath technique and the STBC designs have been performed accordingly . Despite its great academic and industrial success, OFDM suffers from several drawbacks such as large peak to average power ratio and high sensitivity to carrier frequency offsets …”
Section: Introductionmentioning
confidence: 99%
“…In order to address the OFDM limitations, SC‐FDE has already been used as an alternative for communications over multipath channels . Similar to OFDM, SC‐FDE is a cyclic prefix (CP)–based technique that utilizes computationally efficient blocks of fast Fourier transform (FFT) and inverse FFT (IFFT) at the receiver side .…”
Section: Introductionmentioning
confidence: 99%